Development and validation of a prediction model for identifying men with intermediate- or high-risk prostate cancer for whom bone imaging is unnecessary: a nation-wide population-based study. (2nd November 2019) - Godtman, Rebecka Arnsrud; Månsson, Marianne; Bratt, Ola; Robinsson, David; Johansson, Eva; Stattin, Pär; Kjölhede, Henrik
Abstract: Objective: To develop and validate a nomogram that identifies men for whom bone scan is unnecessary. Material and methods: The study datasets were derived from the National Prostate Cancer Register (NPCR) of Sweden. All men in the NPCR ≤80 years of age who were diagnosed with intermediate- or high-risk prostate cancer and who had pretreatment bone imaging ( 99m Tc MDP scintigraphy, plain x-ray, computed tomography, magnetic resonance imaging, and/or positron emission tomography fused with computed tomography) were included. Men diagnosed from 2015–2016 formed a development dataset and men diagnosed in 2017 formed a validation dataset. Outcome was metastasis on bone imaging as registered in NPCR. Multivariable logistic regression was used to develop a nomogram. Results: In the development dataset 482/5084 men (10%) had bone metastasis, the corresponding percentage in the validation dataset was 282/2554 (11%). Gleason grade group, clinical T stage, and prostate-specific antigen were included in the final model. Discrimination and calibration were satisfactory in both the development (AUC 0.80, 95% CI 0.78–0.82) and validation dataset (AUC 0.80, 95% CI, 0.77–0.82). Compared with using the EAU guidelines' recommendation for selecting men for imaging, using the nomogram with a cut-off at 4% chance of bone metastasis, would have avoided imaging in 519/2068 men (25%) and miss bone metastasis in 10/519 (2%) men in the validation dataset. Conclusion: By use of our nomogram, bone scans of men with prostate cancer can be avoided in a large proportion of men.